Three-electron interatomic coulombic decay from the inner-valence double-vacancy states in NeAr - Ouchi, Toshihiko; Sakai, K.; Fukuzawa, H.; Liu, X.-J.; Higuchi, I.; Tamenori, Y.; Nagaya, K.; Iwayama, H.; Yao, M.; Zhang, D.; Ding, D.; Kuleff, Alexander I.; et al. (Physical review letters, 2011)
We have unambiguously identified interatomic Coulombic decay in NeAr from the inner-valence double-vacancy state Ne−Ar2+(3s−2) to outer-valence triple-vacancy states Ne+(2p−1)−Ar2+(3p−2) by momentum-resolved electron-ion multicoincidence. This is the first observation of interatomic Coulombic decay where three electrons (3e) participate. The results suggest that this 3e interatomic Coulombic decay is significantly faster than other competing processes like fluorescence decay and charge transfer via curve crossing.
Gesehen am 19.10.2022